THE RELATIONSHIP OF MOTHER'S KNOWLEDGE AND ATTITUDE REGARDING THE PROGRAM PCV IMMUNIZATION WITH PCV IMMUNIZATION STATUS IN INFANTS AT PAMANDEGAN HEALTH CENTER - Restiani, Rina; Yuningsih, Sukarni Setya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Efforts that can be made to prevent pneumonia include the use of the Pneumococcal Conjugate Vaccine (PCV). Based on the results of interviews at thePANandegan Community Health Center, it was found that 7 out of 10 mothers did not know about PCV immunization and the benefits of this immunization. The aimof this research is to determine the relationship between mothers' knowledge and attitudes about the PCV immunization program with the PCV immunization status of babies in thePANandegan Community Health Center working area. Research MethodsThe method used in this research is quantitative with an observational approach. The research design used in this research is cross sectional. The population required in this study is the community in the working area of the Uncle Health Center, with a total of 10 people. In this study, researchers took a sample of 100 respondents. Sample collection in this study applied a purposive sampling technique. Research ResultsThe research results show that there is a relationship between mother's knowledge and attitudes about the PCV immunization program with PCV immunization status with a significant value of 0.002. The conclusions and suggestionsof this research can be used as a source of reference and sufficient understanding to improve the service capacity of thePANandegan Community Health Center.